2003
DOI: 10.1253/circj.67.757
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of BMIPP Uptake and Regional Wall Motion in Insulin Resistant Patients Following Angioplasty for Acute Myocardial Infarction

Abstract: The effect of insulin resistance (IR) on the fatty acid metabolism of myocardium, and therefore on the recovery of left ventricular (LV) wall motion, has not been established in patients with acute myocardial infarction (AMI). A total of consecutive 58 non-diabetic AMI patients who had successfully undergone emergency coronary angioplasty were analyzed retrospectively. They were categorized into 2 groups, normal glucose tolerance (NGT) and impaired glucose tolerance (IGT), based on a 75-g oral glucose toleranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Echocardiography, 12,13 a flow pattern study of magnetic resonance imaging, 14 electron-beam CT, 15,16 conventional left ventriculography 17,18 and aortography have all been used to evaluate of cardiovascular blood flow, but they all use pulsating 2-D images only, which make it difficult to observe the 3-D spatial relationships circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiography, 12,13 a flow pattern study of magnetic resonance imaging, 14 electron-beam CT, 15,16 conventional left ventriculography 17,18 and aortography have all been used to evaluate of cardiovascular blood flow, but they all use pulsating 2-D images only, which make it difficult to observe the 3-D spatial relationships circulation.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that subclinical deterioration of myocardial perfusion in the at-risk area has etiological and prognostic implications in post-MI patients. Asymptomatic progression or recurrence of myocardial ischemia, deterioration of cardiac function because of sustained impairment of energy metabolism, 1,2,[8][9][10][11] and accelerated remodeling 23 might be responsible for worsening myocardial perfusion.…”
Section: Serial Risk Assessment With Perfusion -Bmipp Imaging In Postmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Impaired fatty acid uptake relative to myocardial perfusion (ie, perfusion -BMIPP mismatch profile) indicates metabolically damaged, dysfunctional but viable myocardium in the risk area, such as stunned myocardium, following coronary revascularization in the acute stage. 2,[8][9][10][11] However, the size of both the BMIPP defect and the perfusion -BMIPP mismatch closely correlate with fatal and non-fatal cardiac events in postmyocardial infarction (MI) patients during long-term follow-up. 12,13 Experiments have shown that myocardial fattyacid metabolism is so sensitive to ischemia that fatty acid uptake is rapidly impaired in relation to a decrease in the myocardial content of high-energy phosphate.…”
mentioning
confidence: 99%
“…Mean time from onset of infarction to reperfusion was 5±6 h (range 0. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Coronary stents were implanted in all patients (MULTI-LINK in 2 cases, GFX in 1 case, and NIR in 8 cases).…”
Section: Patientsmentioning
confidence: 99%
“…Semiquantitative visual analysis was performed by assigning regional tracer defect scores using a 4-point scale (defect score; DS; 0= normal uptake, 1= mildly reduced uptake, 2= severely reduced uptake, and 3= defect). 17 Segments were analyzed for systolic wall thickening and endocardial wall motion using QGS, and were graded as dyskinesis (-1) or as showing akinesis (0), severe hypokinesis (1), moderate hypokinesis (2), mild hypokinesis (3), or normokinesis (4) as the wall motion score (WMS). 15,[18][19][20] Improvement of wall motion was defined as an increase of 1 point or more in WMS over the 6 months.…”
Section: Spect and Pet Analysesmentioning
confidence: 99%